Urinary clusterin levels in the rat correlate with the severity of tubular damage and may help to differentiate between glomerular and tubular injuries - Hidaka, Sumi; Kränzlin, Bettina; Gretz, Norbert; Witzgall, Ralph (Cell & tissue research, 2002)
Clusterin is a secreted glycoprotein that is synthesized after several types of tubular injury. We therefore wondered whether the urinary excretion of clusterin could serve as a parameter to determine the severity of tubular damage. Using an affinity-purified rabbit antiserum raised against recombinant clusterin, we established an enzyme-linked immunosorbent assay to measure the urinary excretion of clusterin after bilateral renal ischemia, in the (cy/+) rat model of autosomal-dominant polycystic kidney disease and in the FHH rat model of focal segmental glomerulosclerosis. After bilateral renal ischemia, the urinary excretion of clusterin paralleled the excretion of total protein and albumin and correlated with the extent of tubular damage. Male (cy/+) rats, but not female (cy/+) rats, excreted more clusterin than age-matched (+/+) rats, a finding consistent with the more rapid course of the disease in males. FHH rats presented with pronounced proteinuria and albuminuria but did not excrete increased levels of clusterin. Urinary clusterin levels could therefore serve as a valuable marker for the severity of tubular damage. Furthermore, clusterin may also help to differentiate between tubular and glomerular forms of proteinuria.
Gesehen am 20.06.2022